Penguatan Kompetensi Numerasi Dan Literasi Digital Guru Sds It Az-Zahra Demak - Wahyuni, Arie; Hidayati, Destia Wahyu; Kurniati, Lenny; Kusumawati, Ratih (Bengawan : Jurnal Pengabdian Masyarakat, 2024)
This article aims to determine the strengthening of the numeracy and digital literacy competencies of SDS IT Az-Zahra Demak teachers. The research method used is a qualitative research method with a field research approach. Research techniques include observation, interviews, and documentation. The result of community service in terms of strengthening teachers' numeracy and digital literacy competencies is the collaboration of all parties, including school principals, teachers, parents and students, to openly provide constructive suggestions and input for the progress of the school, in addition to providing provision in the form of training and workshops. digital. Strengthening in community service activities is provided in the form of workshops and training on digital teaching materials, learning methods and teacher abilities in numeracy and digital literacy competencies. This community service strategy was developed by teachers in terms of strengthening teachers' numeracy and literacy competencies. Strengthening material regarding numeracy and digital literacy competencies can also shape teachers' character and create innovations in digital-based learning materials.